Enhancing pupils' understanding via discussion based POE method - Siris, Ahmet Bahadir; Costu, Bayram (UNIV PERUANA UNION, 2024)
The Predict -Observe -Explain method (POE) stands out as an efficient method in order to overcome misconceptions in human understanding. This approach is characterized by its flexibility and variability. Researchers have created an altered version of the POE which is based on discussion and therefore called discussionbased POE (short POE -DE). The current research aims to examine the effect of this teaching method by reviewing students' academic success and the remediation of misconceptions. A total of 63 eight -graders (aged 12-14 years) took part in the underlying study. 32 pupils were part of the experimental group participating in courses with POE -DE based activities. The remaining 31 represented the control group with teaching activities in line with the current science curriculum. The subject of the unit was Simple Machines . The Simple Machines Academic Achievement Test (AAT) was employed to measure the change in the students' academic accomplishmen. The two-tier Simple Machines Conceptual Test (SMCT) was administered to determine the students' misconceptions and observe whether they had been rectified. According to the statistical data, POE -DE based teaching activities had a substantial impact on both the academic success rate and SMCT scores of the students.
Keywords: misconception; science education; simple machines; predict-observe-explain method; CONCEPTUAL CHANGE; SCIENCE; MISCONCEPTIONS; ELECTROCHEMISTRY; BIOLOGY; MATTER; Education & Educational Research